2018
DOI: 10.1039/c8cc06444j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of symmetrical and unsymmetrical triarylpyrylium ions via an inverse electron demand Diels–Alder reaction

Abstract: One-pot, scalable synthesis of symmetrical and unsymmetrical 2,4,6-triarylpyrylium ions via a highly regioselective inverse electron demand Diels–Alder (IEDDA) reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…26 Recently, Fathimath Salfeena et al reported the synthesis of an unsymmetrical triarylpyrylium ion through the inverse electron demand Diels−Alder (IEDDA) reaction with moderate yields. 27 However, the lack of bridging between donors and acceptors and additional γ-substituted aryl motifs cause a nonradiative transition. To overcome these limitations, we synthesized a pentacyclic pyrylium (PY) fluorophore with bridging cyclohexyl rings using a diverse range of catalysts, and perchloric acid (70%) was found to be the most promising catalyst among 16 catalysts considering the reaction time, purification, and the product yields (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Recently, Fathimath Salfeena et al reported the synthesis of an unsymmetrical triarylpyrylium ion through the inverse electron demand Diels−Alder (IEDDA) reaction with moderate yields. 27 However, the lack of bridging between donors and acceptors and additional γ-substituted aryl motifs cause a nonradiative transition. To overcome these limitations, we synthesized a pentacyclic pyrylium (PY) fluorophore with bridging cyclohexyl rings using a diverse range of catalysts, and perchloric acid (70%) was found to be the most promising catalyst among 16 catalysts considering the reaction time, purification, and the product yields (Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The γ-substituted triarylpyrylium derivative using acetophenone and dypnone was also reported to be in very low yields . Recently, Fathimath Salfeena et al reported the synthesis of an unsymmetrical triarylpyrylium ion through the inverse electron demand Diels–Alder (IEDDA) reaction with moderate yields . However, the lack of bridging between donors and acceptors and additional γ-substituted aryl motifs cause a nonradiative transition.…”
Section: Resultsmentioning
confidence: 99%
“…Hence it has been proved by several calculations [10][11][12] and experiments [13,14] that BF 3 is a highly efficient catalyst for the iEDDA reactions [1]. At the same time, based on experimental results reported in the previous study, the reaction could produce the product with up to 82% yield in the presence of BF 3 [4].…”
Section: Introductionmentioning
confidence: 86%
“…In 2017, You reported an elegant C–H activation/annulation reaction for the one-pot synthesis of fused pyrylium cations . Recently, Sasidhar demonstrated the synthesis of triarylpyrylium via an inverse-electron-demand Diels–Alder reaction . Although great progress has been achieved, the rapid assembly of pyryliums with tunable substituents still would be advantageous.…”
mentioning
confidence: 99%